294. Interim Analysis of an Evidence-Based Bundle Intervention for Uncomplicated Enterobacterales Bacteremia. (31st December 2020) - Stallsmith, Jena; Won, Regina; Lopez, Christopher M; Orme, Forrest; Turner, R Brigg; Chan, Dominic
Abstract: Background: Use of evidence-based process bundles for Staphylococcus aureus bacteremia benefit patient outcomes. No studies exist assessing the value of an evidence-based bundle (EBB) in Enterobacterales bacteremia. Recent studies show shorter durations of therapy (DOT) (~ 7 days) result in similar outcomes as longer DOT when treating uncomplicated gram-negative bacteremia. An internal study showed 87% of treatment course durations were > 7 days. This study seeks to determine the impact of an education-based EBB for uncomplicated Enterobacterales bacteremia on patient length of stay (LOS) and DOT. Methods: This is a quasi-experimental pre- post- analysis conducted across six medical centers. The pre-intervention cohort (n=546) consisted of patients treated for uncomplicated Enterobacterales bacteremia between Jan 1 2016 and Dec 31 2017. The post-EBB education cohort (n=49) consisted of patients treated with the bundle from Jan 1 2020 through Apr 4 2020. Exclusion criteria included immunocompromised state, multiple infection sites, lack of source control, polymicrobial bacteremia, death within 48 hours of treatment, receiving end of life care, < 6 days or > 16 days of therapy, and failure to receive at least one antibiotic with in vitro activity against the organism. The primary outcome was the proportion of patients receiving 6–10 days of therapy. Secondary outcomes included LOS, 30-day readmission rate, 30-day all-cause mortality, time to intravenous to oral conversion, and EBB adherence. Descriptive statistics were used for the baseline characteristics and primary and secondary outcomes. Multiple regression analysis was performed to assess patient covariates. Results: There was no difference in the proportion of patients receiving 6–10 days of therapy between the pre- and the post-EBB groups (43.4% vs 53.1%; p = 0.19). There was no association between DOT and covariates. The pre- and post-intervention group had average total DOT of 11.7 ± 2.6 days and 10.6 ± 2.7 days ( p = 0.0047), respectively. Conclusion: This interim analysis suggests an education-based EBB for Enterobacterales does not increase the proportion of patients receiving DOT of 6–10 days. Education alone may be insufficient. Disclosures: All Authors : No reported disclosures